BMI Trajectories from Childhood to Midlife are Associated with Subclinical Kidney Damage in Midlife. Issue 6 (16th April 2021) - Liu, Conghui; Tian, Jing; Jose, Matthew D.; Dwyer, Terence; Venn, Alison J.
Abstract : Objective: This study aimed to investigate the relationship of BMI trajectories from childhood with subclinical kidney damage (SKD) in midlife, a surrogate measure for chronic kidney disease. Methods: The study followed up 1, 442 participants from the 1985 Australian Schools Health and Fitness Survey who were between 7 and 15 years old at the time the survey was conducted and who had BMI measurements in childhood and at least two follow‐ups in adulthood. Measures of kidney function for participants 36 to 50 years old were also included. Latent class growth mixture modeling was used to identify the BMI trajectories. Log‐binomial regression determined the associations of BMI trajectories with SKD defined as either 1) an estimated glomerular filtration rate (eGFR) of 30 to 60 mL/min/1.73 m 2 or 2) an eGFR > 60 mL/min/1.73 m 2 with a urine albumin‐creatinine ratio ≥ 2.5 mg/mmol (males) or 3.5 mg/mmol (females), adjusting for childhood age, sex, and duration of follow‐up. Results: Relative to the persistently low trajectory ( n = 534, 37.0%), being in higher BMI trajectories was associated with greater risk of SKD in midlife (relative risk [RR] = 1.89, 95% CI = 1.10‐3.25 for progressing to moderate [ n = 633, 43.9%]; RR = 1.91, 95% CI = 0.95‐3.81 for progressing to moderate/high [ n = 194, 13.5%]; RR = 2.86, 95% CI = 1.03‐7.99 for progressing to high/very high [ n = 39, 2.7%]; and RR = 2.47, 95% CI = 0.77‐7.94 for adult‐onset high [ n = 35, 2.4%]). Conclusions: Participants with increasing BMI trajectories from childhood had an increased risk of SKD in midlife.